DIGITALISATION OF TAX : REPORTINGAN ANALYSIS OF E-FILING IN SYSTEMS DIFFERENT COUNTRIES - Hotmaria Hertawaty Sijabat; Fittry Megasari Sijabat (RADJA PUBLIKA, 2025)
This research analyses the implementation of E-Filing systems as part of the digitalisation of tax reporting in various countries and its impact on tax administration. Digitalisation of tax reporting has shown significant benefits in terms of improving the efficiency and accessibility of the reporting processprocess , reducing the time and cost required to tax reports. additionIn, E-Filing systems have been shown to improve taxpayer compliance by making the reporting process easier and more accurate through features such as automated forms and data . validationResearch also shows that E-Filing improves transparency and oversight through better data analysis, allowing tax authorities to detect and address non-compliance more effectively. Overall, the introduction of E-Filing in various countries has been an important step towards a more modern, efficient, and reliable tax system.